2012
DOI: 10.4172/2157-7609.1000124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subacute and Subchronic Treatment of Synthetic Plant Growth Regulators on Liver Damage Serum Biomarkers Tissue Antioxidant Defense Systems and Lipid Peroxidation in Rats

Abstract: The present study was aimed to investigate the effects of some synthetic plant growth regulators; ß-Naphthoxy acetic acid (ß-NOA) and 4-Chlorophenoxy acetic acid (4-CPA) at 10 and 20 ppm dosages on liver damage, antioxidant defense system and lipid peroxidation in rats. Rats were divided into 12 groups as control, ß-NOA and 4-CPA at 10 and 20 ppm dosages application groups. Serum marker enzymes and biochemical parameters were selected as biomarkers for liver damage. Antioxidant defense systems as SOD, GR, CAT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The tissues were homogenized in ultrasonic homogenizer for 5 minutes (Jencons Scientific Co., Bedfordshire, UK, 20 kHz frequency ultrasonic,). The homogenates were centrifuged in a cooled centrifuge device (Hettich Universal 320 R) at 9500 rpm for 30 min at 4 o C. Alphaglucosidase enzyme activity was measured in the supernatants obtained from small intestine tissues [13].…”
Section: Preparation Of Tissue Supernatantmentioning
confidence: 99%
“…The tissues were homogenized in ultrasonic homogenizer for 5 minutes (Jencons Scientific Co., Bedfordshire, UK, 20 kHz frequency ultrasonic,). The homogenates were centrifuged in a cooled centrifuge device (Hettich Universal 320 R) at 9500 rpm for 30 min at 4 o C. Alphaglucosidase enzyme activity was measured in the supernatants obtained from small intestine tissues [13].…”
Section: Preparation Of Tissue Supernatantmentioning
confidence: 99%
“…Although some experiments were performed on animals or cell cultures in vitro for assessment of the PGRs' harmful impacts on animal and human (Folkes et al 1999;Celik et al 2006a), knowledge regarding the toxic effects of PGRs on mammalian organisms is limited or incomplete (Ozok and Celik 2012). Previous studies showed some effects of IAA on biological systems, such as inducing severe cytotoxicity via oxidative stress on lipid membranes and nucleic acids and increasing ROS generation (Folkes and Wardman 2001;de Melo et al 2004).…”
Section: Introductionmentioning
confidence: 99%